Impact-resistant and wear-resistant repair material and preparation method thereof

By optimizing the composition and modification of erosion-resistant and wear-resistant repair materials, the wear and impact damage problems of concrete structures in high-speed water flow environments are solved, the efficient erosion resistance and wear resistance of the materials are achieved, and the service life is extended.

CN120736849AActive Publication Date: 2025-10-03GANSU CIVIL ENG SCI RES INST

Patent Information

Application Number
CN202511251776.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-03
Publication Date
2025-10-03
Estimated Expiration
2045-09-03

AI Technical Summary

Technical Problem

Existing concrete structures face serious surface wear and impact damage problems under high-speed water flow erosion environments. Traditional repair materials are difficult to simultaneously meet the requirements of impact resistance, wear resistance and bonding strength, resulting in a shortened service life.

Method used

The repair material consists of silicate cement, fly ash, quartz sand, silica powder and composite modified carbon fiber. The mechanical properties and wear resistance of the material are enhanced through composite modified carbon fiber surface treatment and organic polymer coating, and CaZrO3 particles are formed by hydrothermal method to improve the mechanical bite force between carbon fiber and cement matrix.

Benefits of technology

It significantly improves the material's erosion resistance and wear resistance, enhances the material's mechanical properties and construction performance, and is suitable for repair projects that are subject to mechanical impact or wear environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of building repairing materials, and particularly discloses an anti-impact and wear-resistant repairing material and a preparation method thereof.By optimizing the content of all the components of the raw materials, the prepared repairing material has excellent anti-erosion performance and wear-resistant performance, Portland cement serves as a main cementing material, and the anti-impact and wear-resistant performance of the repairing material is improved; basic strength and cohesiveness are provided; fly ash and silicon powder synergistically enhance compactness and durability; quartz sand is used as wear-resistant aggregate, so that the compression resistance and the wear resistance are improved; the toughness and the impact resistance are enhanced by the composite modified carbon fibers; the redispersible latex powder improves the flexibility and the binding power; the polycarboxylate superplasticizer optimizes the flowability and improves the compactness; and the defoaming agent reduces pore defects and ensures material uniformity. The repair material provided by the invention is suitable for repair engineering needing to bear mechanical shock or wear environment, and has good construction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building repair materials, and in particular to an impact-resistant and wear-resistant repair material and a preparation method thereof. Background Art

[0002] In water conservancy projects, coastal protection, and water pipelines, concrete structures are exposed to high-speed water erosion containing sand and gravel for a long time, facing serious surface wear and impact damage. Sand and gravel particles, carried by the water flow, repeatedly collide with the concrete surface, not only causing the surface mortar to peel off and the aggregate to be exposed, but also forming pits and cracks on the surface of the structure, which in turn accelerates the corrosion of internal steel bars and the degradation of overall performance. This continuous wear and local stress concentration phenomenon significantly shortens the service life of concrete structures, especially in harsh working conditions with high flow rates and high sediment content. The impact and wear resistance of traditional concrete can no longer meet the engineering requirements, and there is an urgent need to develop repair materials with long-term protective capabilities.

[0003] At present, the repair mortars commonly used in engineering projects are mainly based on ordinary cement-based materials. Their hardness and toughness are difficult to balance, and they are prone to brittle cracking or peeling under dynamic impact loads. Although some modified mortars improve their adhesion by adding polymers or fibers, there are still problems such as insufficient bonding strength with the concrete interface and wear resistance that decays over time.

[0004] Chinese patent document CN115073107A discloses a method for preparing impact-resistant, corrosion-resistant and environmentally friendly mortar. The above-mentioned method effectively improves the synergistic effect between the raw materials through the selection and matching of raw materials, as well as the adjustment of the preparation process and steps, maximizes the optimization of the raw materials and their proportions of cement mortar, and enhances the impact resistance and corrosion resistance of cement mortar. However, the wear resistance of the prepared mortar still needs to be further improved. Summary of the Invention

[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide an impact-resistant and wear-resistant repair material and a preparation method thereof. The prepared repair material has excellent mechanical properties, erosion resistance and wear resistance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: An impact-resistant and wear-resistant repair material is composed of the following raw materials in parts by weight: 150-200 parts of silicate cement, 40-60 parts of fly ash, 360-480 parts of quartz sand, 25-50 parts of silicon powder, 15-25 parts of composite modified carbon fiber, 10-20 parts of redispersible latex powder, 10-15 parts of polycarboxylic acid-based water reducer, 0.5-1 part of defoaming agent, and 60-80 parts of water.

[0007] In the technical solution disclosed in the present invention, silicate cement is used as the main cementitious material to provide basic strength. The proportion of silicate cement can be selected from 150 parts, 160 parts, 170 parts, 180 parts, 190 parts, and 200 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0008] In the technical solution disclosed in the present invention, fly ash is used as an active mineral admixture to participate in secondary hydration reaction to improve strength and durability. The number of fly ash parts can be selected as 40 parts, 45 parts, 50 parts, 55 parts, and 60 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0009] In the technical solution disclosed in the present invention, quartz sand serves as aggregate, mainly playing a role of skeleton support, enhancing the compressive strength and wear resistance of the material. The number of parts of quartz sand can be selected from 360 parts, 370 parts, 380 parts, 390 parts, 400 parts, 410 parts, 420 parts, 430 parts, 440 parts, 450 parts, 460 parts, 470 parts, and 480 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0010] In the present invention, the quartz sand is graded into three levels: 10-20 mesh, 20-40 mesh, and 40-70 mesh, and the mass ratio of each level of quartz sand is 1-2:1-2:1-2.

[0011] In the technical solution disclosed in the present invention, silicon powder serves as an active material to fill micropores and accelerate hydration, thereby improving density and early strength. The amount of silicon powder can be selected from 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, and 50 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0012] In the technical solution disclosed in the present invention, the number of composite modified carbon fibers can be selected from 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, and 25 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] In the technical solution disclosed in the present invention, the preparation method of the composite modified carbon fiber is as follows: S1. Add an emulsifier and tert-dodecyl mercaptan to deionized water and mix well. Then add styrene, hexafluorobutyl acrylate and vinyltriethoxysilane and stir well. Then, heat to 50-60° C., add an initiator, and stir to react to obtain a composite emulsion. S2. dissolving the calcium salt and the zirconium salt in deionized water, then adding the pretreated carbon fiber thereto and dispersing the mixture uniformly, adjusting the pH of the solution to 10-12, performing a hydrothermal reaction, and then drying, calcining, and grinding to obtain a carbon fiber composite material; S3. Dispersing the carbon fiber composite material in the composite emulsion, adjusting the pH of the solution to 4-5, stirring, and then centrifuging, washing, and drying to obtain the composite modified carbon fiber.

[0014] Specifically, in step S1, the mass ratio of the emulsifier, tert-dodecyl mercaptan, deionized water, styrene, hexafluorobutyl acrylate, vinyltriethoxysilane and initiator is 3-5:1-3:100-120:20-25:15-20:10-15:0.5-1.

[0015] More specifically, the emulsifier is selected from at least one of sodium lauryl sulfate, sodium dodecylbenzene sulfonate, and alkylphenol polyoxyethylene ether.

[0016] More specifically, the initiator is selected from persulfates, for example, ammonium persulfate, sodium persulfate or potassium persulfate.

[0017] In step S1, styrene, hexafluorobutyl acrylate and vinyl triethoxysilane are copolymerized through emulsion polymerization to form a composite emulsion, wherein styrene provides a rigid benzene ring structure, and fluorine-containing groups are introduced through hexafluorobutyl acrylate, thereby improving the chemical stability and wear resistance of the material in corrosive media. At the same time, the fluorocarbon segment has a certain flexibility and can absorb part of the kinetic energy through elastic deformation of the molecular chain when impacted, thereby reducing stress concentration; the siloxane group of vinyl triethoxysilane can be hydrolyzed and condensed, and chemically bonded with the -OH on the surface of the carbon fiber composite material, thereby enhancing the interfacial bonding force between the composite emulsion and the carbon fiber.

[0018] Specifically, in step S2, the mass ratio of the calcium salt, the zirconium salt and the pretreated carbon fiber is 3-5:10:4-6.

[0019] The calcium salt is selected from soluble calcium salts, for example, calcium nitrate or calcium chloride.

[0020] The zirconium salt is selected from soluble zirconium salts, for example, zirconium nitrate, zirconium chloride or zirconyl nitrate.

[0021] Specifically, the preparation process of the pretreated carbon fiber is as follows: adding the carbon fiber to a sulfuric acid solution, heating and stirring the solution, thereby obtaining the pretreated carbon fiber.

[0022] Specifically, in step S2, the temperature of the hydrothermal reaction is 150-180°C, for example, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, and 180°C can be selected; the time of the hydrothermal reaction is 3-6h, for example, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, and 6h can be selected, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] Specifically, in step S2, the calcination temperature is 900-1000°C, for example, 900°C, 920°C, 940°C, 950°C, 960°C, 980°C, and 1000°C can be selected; the calcination time is 2-3h, for example, 2h, 2.5h, and 3h can be selected, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] In step S2, a CaZrO3 precursor is first formed on the surface of the pretreated carbon fiber by a hydrothermal method, and then calcined to form a CaZrO3 phase on the surface of the carbon fiber. CaZrO3 particles are dispersed on the surface of the carbon fiber as a hard phase to form a rough structure, which enhances the mechanical bite force between the carbon fiber and the cement matrix, reduces interfacial slip, and improves the mechanical properties of the material. At the same time, it can also effectively reduce the wear of the carbon fiber, thereby improving the wear resistance of the material. In addition, CaZrO3 has extremely high stability to corrosive media in the airflow, further improving the erosion resistance of the carbon fiber.

[0025] Specifically, in step S3, the usage ratio of the carbon fiber composite material and the composite emulsion is 5-10 g:100 mL, for example, 5 g:100 mL, 6 g:100 mL, 7 g:100 mL, 8 g:100 mL, 9 g:100 mL, and 10 g:100 mL can be selected, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In step S3, stirring is performed under weakly acidic conditions (pH 4-5). In the acidic environment, vinyl triethoxysilane is hydrolyzed to form silanol (Si-OH), which chemically bonds with the -OH on the surface of the carbon fiber composite material, thereby coating the surface of the carbon fiber composite material with an organic polymer. This not only improves the dispersion of the carbon fiber in the cement matrix, but also effectively buffers impact energy when subjected to force, reduces interface defects between the carbon fiber and the matrix, and thus significantly improves the mechanical properties and wear resistance of the material.

[0027] In the technical solution disclosed in the present invention, the redispersible latex powder can enhance flexibility, adhesion and impermeability. The number of parts of the redispersible latex powder can be selected as 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, and 20 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0028] In the technical solution disclosed in the present invention, the polycarboxylic acid water-reducing agent reduces the water-cement ratio without affecting the fluidity. The amount of the polycarboxylic acid water-reducing agent can be selected from 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, and 15 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0029] In the technical solution disclosed in the present invention, the defoaming agent can inhibit the generation of bubbles during stirring and avoid pore defects. The amount of the defoaming agent can be selected from 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, and 1 part, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0030] In the technical solution disclosed in the present invention, the number of parts of water can be selected as 180 parts, 190 parts, 200 parts, 210 parts, and 220 parts, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable.

[0031] The present invention also provides a method for preparing the above-mentioned impact-resistant and wear-resistant repair material, comprising the following steps: weighing each raw material according to the formula amount, mixing silicate cement, fly ash, quartz sand, silicon powder and composite modified carbon fiber evenly, then adding redispersible latex powder, polycarboxylic acid water reducer, defoaming agent and water thereto, and continuing to mix evenly to obtain the impact-resistant and wear-resistant repair material.

[0032] Compared with the prior art, the present invention has the following beneficial effects: (1) By optimizing the content of each raw material component, the repair material prepared by the present invention has excellent erosion resistance and wear resistance. Portland cement is used as the main cementitious material to provide basic strength and adhesion; fly ash and silica fume synergistically enhance density and durability; quartz sand is used as wear-resistant aggregate to improve compression and wear resistance; composite modified carbon fiber enhances toughness and impact resistance; redispersible latex powder improves flexibility and adhesion; polycarboxylic acid water reducer optimizes fluidity and improves density; and defoaming agent reduces pore defects and ensures material uniformity. The repair material provided by the present invention is suitable for repair projects that need to withstand mechanical impact or wear environments and has good construction performance.

[0033] (2) The present invention first pre-treats the carbon fiber to enhance the surface roughness of the carbon fiber, which is beneficial to the subsequent loading of CaZrO3 particles. Then, the CaZrO3 particles are dispersed on the surface of the carbon fiber as a hard phase to form a rough structure, which enhances the mechanical bite force between the carbon fiber and the cement matrix, reduces interface slip, and improves the mechanical properties of the material. At the same time, it can also effectively reduce the wear of the carbon fiber, thereby improving the wear resistance of the material. In addition, CaZrO3 has extremely high stability to corrosive media in the air flow, further improving the erosion resistance of the carbon fiber; then, the organic polymer is coated on the surface of the carbon fiber composite material, which not only improves the dispersion of the carbon fiber in the cement matrix, but also effectively buffers the impact energy when subjected to force, reduces the interface defects between the carbon fiber and the matrix, and thus significantly improves the mechanical properties and wear resistance of the material. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0035] It should be noted that, unless otherwise specified, all chemical reagents involved in the present invention were purchased through commercial channels.

[0036] The Portland cement used in the embodiments of the present invention is of P·O 42.5 grade; Fly ash: first-grade fly ash, mesh size is 400 mesh; The quartz sand is graded into 10-20 mesh, 20-40 mesh and 40-70 mesh, and the mass ratio of each grade of quartz sand is 1:1:1; Silica fume: mesh size is 800 mesh; Carbon fiber: 9-13mm in length and 7μm in diameter; The redispersible latex powder comes from Hebei Haoshuo Chemical Co., Ltd. Polycarboxylate water reducer model: PC-1006, from Wuhan Huaxuan High-tech Co., Ltd. Defoamer: Silicone defoamer BYK-088.

[0037] Example 1

[0038] A method for preparing an impact-resistant and wear-resistant repair material comprises the following steps: 180 parts of Portland cement, 50 parts of fly ash, 400 parts of quartz sand, 30 parts of silicon powder and 20 parts of composite modified carbon fiber are mixed evenly, and then 15 parts of redispersible latex powder, 12 parts of polycarboxylic acid water reducer, 0.8 parts of defoaming agent and 200 parts of water are added thereto, and the mixture is continued to be mixed evenly to obtain an impact-resistant and wear-resistant repair material.

[0039] Wherein, the preparation method of the composite modified carbon fiber is as follows: S1, 2g of sodium lauryl sulfate, 2g of alkylphenol polyoxyethylene ether OP-4 and 2g of tert-dodecyl mercaptan were added to 100g of deionized water and mixed uniformly, and then 20g of styrene, 15g of hexafluorobutyl acrylate and 10g of vinyltriethoxysilane were added thereto and stirred uniformly, and then the temperature was raised to 55°C, 0.8g of initiator ammonium persulfate was added, and the reaction was stirred at 55°C for 3h. After the reaction was completed, the mixture was cooled to room temperature to obtain a composite emulsion; S2. Add 10 g of carbon fiber to 100 mL of 40 wt% sulfuric acid solution, stir at 60 ° C for 3 h, filter, wash and dry to obtain pretreated carbon fiber; S3. Dissolve 3 g of calcium nitrate and 10 g of zirconium nitrate in 100 mL of deionized water, then add 5 g of pretreated carbon fiber and disperse evenly. Adjust the pH of the solution to 10 with NaOH solution, perform hydrothermal reaction at 150° C. for 6 h, then filter and dry, calcine at 900° C. for 3 h in a nitrogen atmosphere, and grind to obtain a carbon fiber composite material. S4. Disperse 8 g of carbon fiber composite material in 100 mL of composite emulsion, adjust the pH of the solution to 4 with dilute hydrochloric acid, stir at room temperature for 3 h, and then centrifuge, wash, and dry to obtain composite modified carbon fiber.

[0040] Example 2

[0041] A method for preparing an impact-resistant and wear-resistant repair material comprises the following steps: 150 parts of Portland cement, 40 parts of fly ash, 360 parts of quartz sand, 25 parts of silicon powder and 15 parts of composite modified carbon fiber are mixed evenly, and then 10 parts of redispersible latex powder, 10 parts of polycarboxylic acid water reducer, 0.5 parts of defoaming agent and 180 parts of water are added thereto, and the mixture is continued to be mixed evenly to obtain an impact-resistant and wear-resistant repair material.

[0042] Wherein, the preparation method of the composite modified carbon fiber is as follows: S1, 1g of sodium lauryl sulfate, 2g of alkylphenol polyoxyethylene ether OP-4 and 3g of tert-dodecyl mercaptan were added to 100g of deionized water and mixed uniformly, and then 25g of styrene, 15g of hexafluorobutyl acrylate and 15g of vinyltriethoxysilane were added thereto and stirred uniformly, and then the temperature was raised to 55°C, 1g of initiator ammonium persulfate was added, and the reaction was stirred at 55°C for 3h. After the reaction was completed, the mixture was cooled to room temperature to obtain a composite emulsion; S2. Add 10 g of carbon fiber to 100 mL of 40 wt% sulfuric acid solution, stir at 60 ° C for 3 h, filter, wash and dry to obtain pretreated carbon fiber; S3. Dissolve 5 g of calcium nitrate and 10 g of zirconium nitrate in 100 mL of deionized water, then add 6 g of pretreated carbon fiber and disperse evenly. Adjust the pH of the solution to 10 with NaOH solution, perform hydrothermal reaction at 150° C. for 6 h, then filter and dry, calcine at 900° C. for 3 h in a nitrogen atmosphere, and grind to obtain a carbon fiber composite material. S4. Disperse 5 g of carbon fiber composite material in 100 mL of composite emulsion, adjust the pH of the solution to 4 with dilute hydrochloric acid, stir at room temperature for 3 h, and then centrifuge, wash, and dry to obtain composite modified carbon fiber.

[0043] Example 3

[0044] A method for preparing an impact-resistant and wear-resistant repair material comprises the following steps: 200 parts of Portland cement, 60 parts of fly ash, 480 parts of quartz sand, 50 parts of silicon powder and 25 parts of composite modified carbon fiber are mixed evenly, and then 20 parts of redispersible latex powder, 15 parts of polycarboxylic acid water reducer, 1 part of defoaming agent and 220 parts of water are added thereto, and the mixture is continued to be mixed evenly to obtain an impact-resistant and wear-resistant repair material.

[0045] Wherein, the preparation method of the composite modified carbon fiber is as follows: S1, 2g of sodium lauryl sulfate, 3g of alkylphenol polyoxyethylene ether OP-4 and 3g of tert-dodecyl mercaptan were added to 100g of deionized water and mixed uniformly, and then 20g of styrene, 20g of hexafluorobutyl acrylate and 10g of vinyltriethoxysilane were added thereto and stirred uniformly, and then the temperature was raised to 55°C, 1g of initiator ammonium persulfate was added, and the reaction was stirred at 55°C for 3h. After the reaction was completed, the mixture was cooled to room temperature to obtain a composite emulsion; S2. Add 10 g of carbon fiber to 100 mL of 40 wt% sulfuric acid solution, stir at 60 ° C for 3 h, filter, wash and dry to obtain pretreated carbon fiber; S3. Dissolve 5 g of calcium nitrate and 10 g of zirconium nitrate in 100 mL of deionized water, then add 6 g of pretreated carbon fiber and disperse evenly. Adjust the pH of the solution to 10 with NaOH solution, perform hydrothermal reaction at 150° C. for 6 h, then filter and dry, calcine at 900° C. for 3 h in a nitrogen atmosphere, and grind to obtain a carbon fiber composite material. S4. Disperse 10 g of carbon fiber composite material in 100 mL of composite emulsion, adjust the pH of the solution to 4 with dilute hydrochloric acid, stir at room temperature for 3 h, and then centrifuge, wash, and dry to obtain composite modified carbon fiber.

[0046] Comparative Example 1 A method for preparing an impact-resistant and wear-resistant repair material comprises the following steps: 180 parts of Portland cement, 50 parts of fly ash, 400 parts of quartz sand, 30 parts of silicon powder and 20 parts of composite modified carbon fiber are mixed evenly, and then 15 parts of redispersible latex powder, 12 parts of polycarboxylic acid water reducer, 0.8 parts of defoaming agent and 200 parts of water are added thereto, and the mixture is continued to be mixed evenly to obtain an impact-resistant and wear-resistant repair material.

[0047] Wherein, the preparation method of the composite modified carbon fiber is as follows: S1, 2g of sodium lauryl sulfate, 2g of alkylphenol polyoxyethylene ether OP-4 and 2g of tert-dodecyl mercaptan were added to 100g of deionized water and mixed uniformly, and then 20g of styrene, 15g of hexafluorobutyl acrylate and 10g of vinyltriethoxysilane were added thereto and stirred uniformly, and then the temperature was raised to 55°C, 0.8g of initiator ammonium persulfate was added, and the reaction was stirred at 55°C for 3h. After the reaction was completed, the mixture was cooled to room temperature to obtain a composite emulsion; S2. Add 10 g of carbon fiber to 100 mL of 40 wt% sulfuric acid solution, stir at 60 ° C for 3 h, filter, wash and dry to obtain pretreated carbon fiber; S3. Disperse 8 g of pretreated carbon fiber in 100 mL of the composite emulsion, adjust the pH of the solution to 4 with dilute hydrochloric acid, stir at room temperature for 3 h, and then centrifuge, wash, and dry to obtain a composite modified carbon fiber.

[0048] Compared with Example 1, Comparative Example 1 does not load CaZrO 3 on the pretreated carbon fiber.

[0049] Comparative Example 2 A method for preparing an impact-resistant and wear-resistant repair material comprises the following steps: 180 parts of Portland cement, 50 parts of fly ash, 400 parts of quartz sand, 30 parts of silicon powder and 20 parts of composite modified carbon fiber are mixed evenly, and then 15 parts of redispersible latex powder, 12 parts of polycarboxylic acid water reducer, 0.8 parts of defoaming agent and 200 parts of water are added thereto, and the mixture is continued to be mixed evenly to obtain an impact-resistant and wear-resistant repair material.

[0050] Wherein, the preparation method of the composite modified carbon fiber is as follows: S1. Add 10 g of carbon fiber to 100 mL of 40 wt% sulfuric acid solution, stir at 60 ° C for 3 h, filter, wash and dry to obtain pretreated carbon fiber; S2. Dissolve 3 g of calcium nitrate and 10 g of zirconium nitrate in 100 mL of deionized water, then add 5 g of pretreated carbon fiber and disperse evenly. Adjust the pH of the solution to 10 with NaOH solution, hydrothermally react at 150 ° C for 6 h, then filter and dry, calcine at 900 ° C for 3 h in a nitrogen atmosphere, and grind to obtain a composite modified carbon fiber.

[0051] Compared with Example 1, in Comparative Example 2, only the pretreated carbon fiber was subjected to CaZrO3 loading treatment.

[0052] Comparative Example 3 A method for preparing an impact-resistant and wear-resistant repair material comprises the following steps: 180 parts of Portland cement, 50 parts of fly ash, 400 parts of quartz sand, 30 parts of silicon powder and 20 parts of composite modified carbon fiber are mixed evenly, and then 15 parts of redispersible latex powder, 12 parts of polycarboxylic acid water reducer, 0.8 parts of defoaming agent and 200 parts of water are added thereto, and the mixture is continued to be mixed evenly to obtain an impact-resistant and wear-resistant repair material.

[0053] Wherein, the preparation method of the composite modified carbon fiber is as follows: S1, 2g of sodium lauryl sulfate, 2g of alkylphenol polyoxyethylene ether OP-4 and 2g of tert-dodecyl mercaptan were added to 100g of deionized water and mixed uniformly, and then 20g of styrene, 15g of acrylic acid and 10g of vinyltriethoxysilane were added thereto and stirred uniformly, and then the temperature was raised to 55°C, 0.8g of initiator ammonium persulfate was added, and the reaction was stirred at 55°C for 3h. After the reaction was completed, the mixture was cooled to room temperature to obtain a composite emulsion; S2. Add 10 g of carbon fiber to 100 mL of 40 wt% sulfuric acid solution, stir at 60 ° C for 3 h, filter, wash and dry to obtain pretreated carbon fiber; S3. Dissolve 3 g of calcium nitrate and 10 g of zirconium nitrate in 100 mL of deionized water, then add 5 g of pretreated carbon fiber and disperse evenly. Adjust the pH of the solution to 10 with NaOH solution, perform hydrothermal reaction at 150° C. for 6 h, then filter and dry, calcine at 900° C. for 3 h in a nitrogen atmosphere, and grind to obtain a carbon fiber composite material. S4. Disperse 8 g of carbon fiber composite material in 100 mL of composite emulsion, adjust the pH of the solution to 4 with dilute hydrochloric acid, stir at room temperature for 3 h, and then centrifuge, wash, and dry to obtain composite modified carbon fiber.

[0054] Compared with Example 1, in Comparative Example 3, acrylic acid was used to replace hexafluorobutyl acrylate.

[0055] The repair materials prepared in Examples 1-3 and Comparative Examples 1-3 were prepared into test blocks, and then performance tests were performed, as follows: Compressive strength and flexural strength: The test pieces were cured for 28 days under standard curing conditions, and then tested in accordance with GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete"; Erosion resistance: tested using the underwater steel ball method in DL / T5150-2001 "Test Procedure for Hydraulic Concrete"; Wear resistance test: In accordance with the provisions of "Test Procedures for Cement and Cement Concrete in Highway Engineering" JTGE30-2005 and "Test Method for Abrasion Resistance of Cement Mortar" JC / T421-1991, a wear resistance test was conducted using a TMS-04 cement mortar / concrete wear resistance testing machine with a flower wheel grinding head. The wear resistance after 28 days under standard curing conditions was calculated. The test results are shown in Table 1.

[0056] Table 1 Performance test results of each group

[0057] Finally, it should be noted that the above embodiments do not limit the present invention in any form. Those skilled in the art will appreciate that modifications and improvements can be made based on the present invention. Therefore, any modifications or improvements made without departing from the spirit of the present invention are intended to fall within the scope of protection claimed in the present invention.

Claims

1. An impact-resistant and wear-resistant repair material, characterized in that: The invention is composed of the following raw materials in parts by weight: 150-200 parts of Portland cement, 40-60 parts of fly ash, 360-480 parts of quartz sand, 25-50 parts of silica fume, 15-25 parts of composite modified carbon fiber, 10-20 parts of redispersible latex powder, 10-15 parts of polycarboxylic acid water reducing agent, 0.5-1 part of defoaming agent, and 180-220 parts of water. The preparation method of the composite modified carbon fiber is as follows: S1. Add an emulsifier and tert-dodecyl mercaptan to deionized water and mix well. Then add styrene, hexafluorobutyl acrylate and vinyltriethoxysilane and stir well. Then, heat to 50-60° C., add an initiator, and stir to react to obtain a composite emulsion. S2. dissolving the calcium salt and the zirconium salt in deionized water, then adding the pretreated carbon fiber thereto and dispersing the mixture uniformly, adjusting the pH of the solution to 10-12, performing a hydrothermal reaction, and then drying, calcining, and grinding to obtain a carbon fiber composite material; S3. Dispersing the carbon fiber composite material in the composite emulsion, adjusting the pH of the solution to 4-5, stirring, and then centrifuging, washing, and drying to obtain the composite modified carbon fiber.

2. The impact-resistant and wear-resistant repair material according to claim 1, characterized in that: In step S1, the mass ratio of the emulsifier, tert-dodecyl mercaptan, deionized water, styrene, hexafluorobutyl acrylate, vinyltriethoxysilane and initiator is 3-5:1-3:100-120:20-25:15-20:10-15:0.5-1.

3. The impact-resistant and wear-resistant repair material according to claim 1, characterized in that: In step S1, the emulsifier is selected from at least one of sodium lauryl sulfate and alkylphenol polyoxyethylene ether.

4. The impact-resistant and wear-resistant repair material according to claim 1, characterized in that: In step S1, the initiator is selected from persulfate.

5. The impact-resistant and wear-resistant repair material according to claim 1, characterized in that: In step S2, the mass ratio of the calcium salt, the zirconium salt and the pretreated carbon fiber is 3-5:10:4-6.

6. The impact-resistant and wear-resistant repair material according to claim 1, characterized in that: In step S2, the temperature of the hydrothermal reaction is 150-180° C., and the time of the hydrothermal reaction is 3-6 hours.

7. The impact-resistant and wear-resistant repair material according to claim 1, characterized in that: In step S2, the calcination temperature is 900-1000° C. and the calcination time is 2-3 hours.

8. The impact-resistant and wear-resistant repair material according to claim 1, characterized in that: In step S3, the usage ratio of the carbon fiber composite material and the composite emulsion is 5-10 g:100 mL.

9. The method for preparing the impact-resistant and wear-resistant repair material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: weighing each raw material according to the formula, uniformly mixing silicate cement, fly ash, quartz sand, silicon powder and composite modified carbon fiber, then adding redispersible latex powder, polycarboxylic acid water reducer, defoaming agent and water, and continuing to mix uniformly to obtain an impact-resistant and wear-resistant repair material.

Citation Information

Patent Citations

  • Impact-resistant corrosion-resistant environment-friendly mortar and preparation method thereof

    CN115073107A

  • Ultra-high-performance pier reinforcing and repairing composite material and preparation method thereof

    CN111549655A

  • Low-temperature spraying cement-based mortar material for trenchless pipeline repair and preparation method thereof

    CN112811871A

  • MOF reinforced carbon fiber composite material and preparation method thereof

    CN117646332A

  • Preparation method of regenerated cellulose-based carbon fiber material

    CN118685895A

Cited By

  • Cement-based anti-corrosion and anti-freezing material and preparation method thereof

    CN121107791A